A systematic scoping review of asset-based approaches to promote health in communities: development of a framework. (September 2020) - Cassetti, Viola; Powell, Katie; Barnes, Amy; Sanders, Tom
Asset-based approaches to health promotion have become increasingly popular as a way to tackle health inequalities by empowering people in more disadvantaged communities to use local resources and increase control over health and its determinants. However, questions remain about how they work in practice. This article presents the findings from a systematic scoping review of the empirical literature on asset-based approaches in communities. The aim was to identify the key elements of asset-based approaches, and how they are operationalised in interventions aimed at promoting health and reducing inequalities in local communities. Four databases were searched (Medline, PsycINFO, CINAHL, ASSIA) and papers were included if they described interventions explicitly adopting an asset-based approach but excluded if limited to asset identification. Thirty articles were included in the review. Data were extracted on the type of assets that the intervention built upon, how assets were mobilised, the expected outcomes and evaluation methods. A framework is presented that synthesises the key characteristics of asset-based interventions to promote health in communities. Three main approaches to mobilising assets were identified in the literature: (A) connecting assets, (B) raising awareness of assets and (C) enabling assets to thrive. It is argued that asset-based approaches to health promotion take a wide variety of forms, making it difficult to anticipate outcomes and to evaluate interventions. The framework presented here can be used to better understand the processes through which asset-based approaches work in practice to promote health and reduce inequalities.